2006
DOI: 10.1016/j.disc.2004.12.027
|View full text |Cite
|
Sign up to set email alerts
|

r-Strong edge colorings of graphs

Abstract: Let G be a graph and for any natural number r, s (G, r) denotes the minimum number of colors required for a proper edge coloring of G in which no two vertices with distance at most r are incident to edges colored with the same set of colors. In [Z. Zhang, L. Liu, J. Wang, Adjacent strong edge coloring of graphs, Appl. Math. Lett. 15 (2002) 623-626] it has been proved that for any tree T with at least three vertices, s (T , 1) (T ) + 1. Here we generalize this result and show that s (T , 2) (T ) + 1. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 6 publications
0
44
1
Order By: Relevance
“…The last theorem is weaker than the results of of Akbari et al [1] and Hatami [6] for graphs with large maximum degree.…”
Section: Theorem 8 If G Is a Connected Graph With Maximum Degreecontrasting
confidence: 45%
“…The last theorem is weaker than the results of of Akbari et al [1] and Hatami [6] for graphs with large maximum degree.…”
Section: Theorem 8 If G Is a Connected Graph With Maximum Degreecontrasting
confidence: 45%
“…Hatami [11] showed that if G is a normal graph and ∆(G) > 10 20 , then χ ′ a (G) ≤ ∆(G) + 300. For more references, see [1,3,8,12]. Recently, in [13], Hocquard et al proved the following result.…”
Section: Introductionmentioning
confidence: 78%
“…1. By our assumption, we know that H 1 has an nsd- 3 ). Then we properly color vv 2 and vv 3 such that τ (vv 2 …”
Section: Lemma 1 [21] Every K 4 -Minor Free Graph G With δ(G) ≥ 3 Conmentioning
confidence: 97%